The Economy of Cluj. Cluj-Napoca and the Cluj Metropolitan Area: The development of the Local Economy in the 2008-2018 decade - MOLDOVAN, Darie; MARE, Codruța; PETROVICI, Norbert (2021)
Over the last decade, globalization processes have intensified, and as such, global organizations relocatedtheir secondary processes to new spaces specialized in operations (Peck 2018; Oshri, Kotlarsky, andWillcocks 2015). Most of the processes that are being externalized are Business Process Outsourcing(BPO) and Information Technology Outsourcing (ITO) (Oshri, Kotlarsky, and Willcocks 2015).The global outsourcing hotspots are India, China and the Philippines, that concentrate over 80% ofoutsourced processes. At European level, Central and Eastern Europe has capitalized most of theoutsourcing in the West, particularly in regards to German capital (Marin 2018; Dustmann et al. 2014).Almost half (45.4%) of the total foreign investments of German companies is outsourced to Central andEastern Europe. In Romania 63.7% of the German foreign investments are processes that were outsourcedto our country (Marin, Schymik, and Tarasov 2018).